1999
DOI: 10.1002/(sici)1097-0045(19990615)40:1<28::aid-pros4>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Can histopathology predict treatment outcome following high‐energy transurethral microwave thermotherapy of the prostate? Results of a biopsy study

Abstract: BACKGROUND.Despite good results of high-energy transurethral microwave thermotherapy (TUMT) in the treatment of benign prostatic hyperplasia, it is still difficult to predict the response to treatment on an individual basis. Besides clinical baseline parameters, intrinsic histological parameters are suggested to play a role in the response variance after TUMT. In this study we analyzed histological parameters (vessel density and epithelium-stroma (E/S) ratio) in patients who were selected for high-energy TUMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Factors such as prostatic vessel density and epithelial/stromal ratio seem to be related to the outcome, but the findings are difficult to translate into clinical use. D'Ancona et al [27] found large inter-individual variation, and thus it will be very difficult to establish thresholds of these variables to be used as predictors in each patient. Furthermore, there are no reliable noninvasive methods to measure these 'intrinsic' prostate characteristics, or they are not fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as prostatic vessel density and epithelial/stromal ratio seem to be related to the outcome, but the findings are difficult to translate into clinical use. D'Ancona et al [27] found large inter-individual variation, and thus it will be very difficult to establish thresholds of these variables to be used as predictors in each patient. Furthermore, there are no reliable noninvasive methods to measure these 'intrinsic' prostate characteristics, or they are not fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the distribution of histologic components (epithelium/stromal ratio and blood-vessel density) has been proposed as determinative of the reaction of the prostate to the application of heat. 33 However, no significant difference could be detected for either the epithelial/stromal ratio or vessel density in good and poor responders.…”
mentioning
confidence: 91%
“…The wide range of outcomes in apparently similar patients led to research aiming to establish pretreatment factors that could be used to predict the results. Currently it is thought that small prostate volume, a low grade of obstruction, age, low epithelial/stromal ratio, low PSA level, low energy delivery and high prostate vascularity are independent predictors of a poor outcome [13–15].…”
Section: Introductionmentioning
confidence: 99%